Comparison of the iterative jacobi method and the iterative Domain Green'S Function Method for finite array analysis - Ludick, D.; Botha, M.; Maaskant, R.; Davidson, David (2016)
© 2016 European Association of Antennas and Propagation. The purpose of this work is to compare two iterative techniques that may be used for the analysis of large, disjoint finite antenna arrays, viz. the iterative Jacobi method and the iterative Domain Green's Function Method. These methods are conceptually similar, in that they offer alternative ways to improve non-local current distributions during the iterative process. The error convergence of each method will be studied at the hand of an example.